KONTRIBUSI ISLAM TERHADAP AKUNTANSI - Ivo Sabrina (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2012)
This study will focus on the comparison between the accounting and another definition to find the harmony and unity of meaning in it. This study uses the approach of the historical development and significance of accounting in Islam. in the perspective of the Quran and Hadith, the meaning of accounting is general and covers the whole of human activity in the lives interact and transact among others, both religious and related fields mu‘âmalah areas and socioeconomic transac-tions in general.DOI: 10.15408/aiq.v4i2.2550